A dusty streamer infalling onto the disk of a class I protostar: ALMA dual-band constraints on grain properties and the mass-infall rate - Cacciapuoti, Luca; Macias, E.; Gupta, A.; Testi, L.; Miotello, A.; Espaillat, C.; Küffmeier, M.; van Terwisga, S.; Tobin, J.; Grant, S.; Manara, C. F.; Segura-Cox, D.; et al. (Astronomy and astrophysics, 2024)
Methods. We detected the extended dust emission from this structure in both ALMA bands. We tested whether the velocity pattern of the streamer is consistent with infalling trajectories by means of analytical streamline models. We measured spectral index maps for the first time and derived a dust opacity-index profile along a streamer. We constrained its grain properties and mass. - Results. We find that the arc structure is consistent with infalling motions. We measure a spectral index α ∼ 3.2 across the entire structure and a dust opacity index β ∼ 1.6. Considering grain properties consistent with the measured β, the structure can host up to 245 M⊕ of dust, which exceeds or is comparable to the mass of the inner unresolved 600 au, which contains the protoplanetary disk of M512. Assuming a typical dust-to-gas ratio of 1% for the streamer, the free-fall timescales (50 kyr) imply total mass-infall rates up to 1.5 × 10−6 M⊙ yr−1. M512 has been classified as an outbursting source with multi-epoch WISE photometry. It is thus an interesting case study for exploring the possible connection between infalling streamers and accretion outbursts. - Conclusions. M512 is a unique source for which dust continuum emission of an arc-like streamer extending out to 4000 au can be characterized in a dual-band analysis. The dust properties are similar to those in the interstellar medium and imply a high dust mass. A massive streamer like this can affect the evolution of the star- and planet-forming inner system strongly.
Gesehen am 29.03.2024